Design and production of electronic newspapers and knowledge communication (Journal of the College of Basic Education, 2023)
Our world today is going through an advanced stage of technologies that mixed with informatics and caused a knowledge explosion in advanced and multiple languages and forms that were controlled by information technology and modern means of communication after passing through multiple stages starting with visual symbols and sign language, ending with computer technology through which information of all kinds was translated into symbols Encrypted and pictorial to deliver news and events, and Internet technologies allowed press institutions to obtain (an encyclopedia of information), and to raise the barriers restricting the press designer in terms of the space specified by the dimensions of the paper and the cost of collecting information. As the media organization plays a key role in forming public opinion because it possesses the elements and mechanisms of the influential language reflected on the recipient to achieve feedback with every communication message, and taking their opinions about the published news and immediate comment on those news and events.